Annual Plan 1982-83 Government of India Planning Commission - Planning Commission (Planning Commission, 1983)
The Annual Plan 1982-83, the third year of India’s Sixth Five-Year Plan, emphasized economic recovery, productivity enhancement, and social welfare. Key priorities included increased public sector outlay, investments in energy, transport, irrigation, and rural development, particularly under the Integrated Rural Development Programme and Minimum Needs Programme. Agricultural objectives targeted foodgrain production, improved irrigation, and fertilizer usage, while industrial development focused on steel, fertilizers, heavy industry, and small-scale enterprises. The plan also addressed communication and broadcasting expansion, regional development for SCs, STs, and hill areas, and scientific and vocational initiatives. Fiscal strategies included resource mobilization, controlled deficit financing, and external assistance. Overall, the plan reflects a comprehensive approach to economic growth, infrastructural improvement, and social upliftment, integrating financial discipline with sectoral development.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Annual Plan; Economic Recovery; Public Sector Outlay; Agriculture; Rural Development; Industrial Growth; Infrastructure; Communications; Social Welfare; Financial Estimates